Fixation of Extraocular Muscles to Porous Orbital Implants Using 2-Ocetyl-Cyanoacrylate Glue. Issue 4 (July 2015) - Warder, Daniel; Kratky, Vladimir
Abstract : Purpose: To assess the efficacy of recti muscle fixation with 2-ocetyl-cyanoacrylate tissue glue to porous orbital implants in human subjects undergoing enucleation. Methods: This was a prospective interventional study with a historical control group. Over a 1-year period, patients who received orbital implant fixation using 2-ocetyl-cyanoacrylate tissue glue were enrolled in the study. Functional assessment was carried out by measurement of implant motility at the 6-month postoperative period, which was compared with a historical control group of patients with sutured implants. Structural assessment was carried out with a random sample of orbital MRIs. Results: Twelve patients received the glue-fixation technique. There were no intraoperative or immediate postoperative complications. There was no statistically significant difference between the glued and sutured groups' horizontal implant movement (7.0 mm ± 1.5 mm vs. 6.8 mm ± 1.8 mm, respectively; p = 0.85) or vertical implant movement (5.6 mm ± 1.7 mm vs. 5.0 mm ± 1.4 mm, respectively; p = 0.39). Sample orbital MRI demonstrated good muscle approximation to the implants as well as contrast enhancement suggestive of successful fibrovascular proliferation. Conclusions: Recti muscle fixation using 2-ocetyl-cyanoacrylate tissue glue to porous orbital implants appeared safe and produced good functional and structural results in this proof-of-concept study. This novel technique of implant fixation may offer benefits in terms of reduced operating room time and cost savings. Abstract : Prospective study demonstrating the efficacy of recti muscle fixation to porous orbital implants, using 2-ocetyl-cyanoacrylate tissue glue, in patients undergoing enucleation.